2009
DOI: 10.2214/ajr.09.2522
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Breast Lesions With Diffusion-Weighted MRI: Comparing the Use of Different b Values

Abstract: Diffusion-weighted imaging is a potential resource as a coadjutant of MRI in the differentiation between benign and malignant lesions. Such imaging can be performed without a significant increase in examination time, especially because it can be done with lower b values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
80
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(97 citation statements)
references
References 31 publications
14
80
0
3
Order By: Relevance
“…A threshold ADC value of 1.30x10 -3 mm 2 /s in the study is compatible with the range of 1.1-1.60x10 -3 mm 2 /s, which has been reported in the literature and helps to distinguish benign vs malignant lesions with 89.1% sensitivity and 100% specificity (15,(22)(23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A threshold ADC value of 1.30x10 -3 mm 2 /s in the study is compatible with the range of 1.1-1.60x10 -3 mm 2 /s, which has been reported in the literature and helps to distinguish benign vs malignant lesions with 89.1% sensitivity and 100% specificity (15,(22)(23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 87%
“…As a consequence, lower b values result in higher ADC values. Although no consensus exists on the appropriate b value, Pereira et al (26) compared the ADC values of malign breast tumors acquired at various b values and reported the ADC values at 750 mm²/s to be more sensitive than lower ones for the estimation of malignant potential (19). Similarly, as the preferred b value at our institution, 750 mm²/s was implemented.…”
Section: Balkanmentioning
confidence: 99%
See 1 more Smart Citation
“…The first study found no significant difference in the diagnostic performance of ADC (42). The optimum cut-off values varied in these studies, which was likely a result of different calculation methods and differences in patient populations (43)(44)(45). Despite the ability of DWI to statistically differentiate benign from malignant breast lesions, there is typically a considerable overlap of values in the two groups.…”
Section: Breast Applicationsmentioning
confidence: 96%
“…The range of b values reported in the literature for breast DWI is 0-1000. Two studies have investigated multiple combinations of b values to determine their effect on image quality and the calculated ADC value (42,43). The first study found no significant difference in the diagnostic performance of ADC (42).…”
Section: Breast Applicationsmentioning
confidence: 99%